FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS REJOSARI - kiki megasari (Jurnal Ilmu Kebidanan, 2018)
ABSTRACT Acute Respiratory Infection (ARI) is an important health problem because it is the first cause of under-five mortality in developing countries. Most cases occur in India (43 million), China (21 million), Pakistan (10 million) and Bangladesh, Indonesia, Nigeria each 6 million episodes. The incidence of ARI in Indonesia is still relatively high, especially in underfives, morbidity rate reaches 3% and mortality rate (mortality) from ARI disease reaches 15.5%. In Pekanbaru, ARI is also a major public health problem. Although in the last 3 years the number of cases has decreased cases, but the incidence is still relatively high. The purpose of this study is to determine the factors associated with the incidence of ARI in Toddlers Rejosari Puskesmas Pekanbaru. This research is type of Quantitative research with research design Correlation Analysis with cross sectional approach. The sample in this research is mothers who have children of children under five who visited Rejosari health center in accordance with inclusion and exclusion criteria amounted to 69 respondents. Data collection through questionnaire distribution with Univariate and Bivariate analysis and chi square statistical test. The results showed that there was a correlation between knowledge of mother with the incidence of ARI with (P Value 0,011 value OR = 4,239), environment (P Value 0,002 value OR = 7,2). And the results showed no relationship between age with the incidence of ARI (P Value 1.000 value OR = 1.014. Keywords: ARI in Toddler, Age Factor, Knowledge, Environment